2012
DOI: 10.1177/193229681200600506
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Levels in Critically Ill Patients: Are Normoglycemia and Low Variability Associated with Improved Outcomes?

Abstract: Results show that OL are higher for patients with cTIB ≥ 0.3-0.7 than patients with cTIB < 0.3-0.7, irrespective of how cTIB was achieved. A cTIB threshold of 0.5 was found to be a minimum acceptable threshold based on outcome. If cTIB is used in similar BG studies in the future, cTIB ≥ 0.7 may be a good target for glycemic control to ensure outcomes and to separate patients with good BG control from patients with poor control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…The TIR 80-110 mg/dL in this investigation, conducted by what many would consider the most experienced team of clinicians performing BG control in the world, was higher in the patients who were treated using the computer-guided protocol but, nevertheless, was only 68.6 versus 60.1%. Chase and collaborators evaluated the relationship of TIR 72-126 mg/dL to mortality in a cohort of 784 patients admitted to a single New Zealand mixed medical-surgical ICU, demonstrating that TIR >70% was independently associated with probability of survival [50]. They subsequently performed a post hoc analysis of data from the Glucontrol trial of IIT [4,51], a study that was terminated prematurely by its oversight board because of protocol violations and the inability of the clinicians to achieve the targeted BG range.…”
Section: Time In Targeted B Rangementioning
confidence: 98%
“…The TIR 80-110 mg/dL in this investigation, conducted by what many would consider the most experienced team of clinicians performing BG control in the world, was higher in the patients who were treated using the computer-guided protocol but, nevertheless, was only 68.6 versus 60.1%. Chase and collaborators evaluated the relationship of TIR 72-126 mg/dL to mortality in a cohort of 784 patients admitted to a single New Zealand mixed medical-surgical ICU, demonstrating that TIR >70% was independently associated with probability of survival [50]. They subsequently performed a post hoc analysis of data from the Glucontrol trial of IIT [4,51], a study that was terminated prematurely by its oversight board because of protocol violations and the inability of the clinicians to achieve the targeted BG range.…”
Section: Time In Targeted B Rangementioning
confidence: 98%
“…Glycaemic control protocols need to be both safe and effective for all patients, and be able to account for patient variability, before potential clinical benefits can be assessed (Penning et al, 2015, Chase et al, 2008a, Krinsley and Preiser, 2015, Signal et al, 2012. Indeed, meta-analysis studies have recently shown that studies where glycaemic protocols achieved the targeted range reported reduced mortality, while others showed no beneficial outcome or increased mortality (Mesotten andVan den Berghe, 2009, Griesdale et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of vasopressors, corticosteroids, enteral or parenteral nutrition -as well as the discontinuation of these therapies due to a variety of procedures performed in critical patients -leads to significant daily variability in glycemic levels. 22 Despite the benefits of adequate glycemic control in critically ill patients, 7,[23][24][25] retrospective studies have shown an association between increased glycemic variability and increased mortality. 22,26 There is a thin threshold between protective care and a potentially harmful approach to the patient, significantly elevating the risk of severe hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%